Fucoidan mitigated diabetic nephropathy through the downregulation of PKC and modulation of NF‐κB signaling pathway: in vitro and in vivo investigations. (2nd December 2020) - Xu, Jingge; Wang, Yan; Wang, Zhen; Guo, Lanping; Li, Xinpeng
Abstract : The persistence of hyperglycemia and oxidative stress in diabetic patients ultimately leads to diabetic nephropathy (DN). In this study, we investigated the effect of sulfated polysaccharides (SPS) extracted from Laminaria japonica in relieving DN symptoms. To induce the diabetic model, normal rats were kept on a high‐sugar, high‐fat diet, then they were injected with streptozocin. Groups of these rats were later treated with SPS and/or protein kinase C (PKC) inhibitor. The analyses performed herein demonstrate that although diabetes significantly decreases the body weights of rats, SPS and inhibitor treatments increase these weights, as well as the ratios of renal to total body weight. Serum biochemical analyses indicate that blood urea nitrogen and serum creatinine levels gradually decrease in the SPS group. In addition, DN symptoms are substantially relieved by SPS and/or inhibitor treatments, as evidenced by histopathological analyses. Changes in the expressions of PKC‐α, PKC‐β, P‐selectin, nuclear factor kappa B (NF‐κB), and p65, detected by immunohistochemistry and western blot assessments, show that SPS regulates diabetic nephropathy via the PKC/NF‐κB pathway.